Предмет: Алгебра,
автор: shabovicharina
решите уравнение
(x +2)(x^2 - 2x + 4) + 3x^2= x^2(x + 3) - 2x
Ответы
Автор ответа:
1
Ответ:
-4
Объяснение:
(x + 2)(x² - 2x +4) + 3x² = x²(x + 3) - 2x
x³ + 8 + 3x² = x³ + 3x² - 2x
x³ + 3x² - x³ - 3x² + 2x= -8
2x = -8
x = -4
shabovicharina:
а как же -2X в конце уравнения? куда он делся
Похожие вопросы
Предмет: Алгебра,
автор: irmtovadasha
Предмет: Українська мова,
автор: gfxde
Предмет: Алгебра,
автор: ionelkira458
Предмет: Литература,
автор: aliya00980
Предмет: Биология,
автор: Идиот21